Extracellular Vesicle-Associated mir-21 and mir-144 Are Markedly Elevated in Serum of Patients With Hepatocellular Carcinoma - Pu, Chunwen (Front Physiol, 2018)
Aim: The aim of this study was to observe the possible change of microRNAs (miRNAs) in serum extracellular vesicles (EVs) from hepatocellular carcinoma (HCC) patients. Methods: The serum EVs were purified from 17 healthy donors, 16 chronic hepatitis B (CHB) patients and 24 HCC patients. The sequenced microRNAs in the purified EVs were analyzed to obtain highly differentially expressed genes (DEGs). Finally, the expression pattern of DEGs was validated using qRT-PCR. Results: We found that the expression of hsa-miR-21-5p and hsa-miR-144-3p were significantly higher in EVs and liver cancer tissues compared with serum and the distal liver tissues in HCC patients. The ratio of hsa-miR-144-3p/hsa-miR-21-5p was significantly decreased in the patients with CHB but significantly increased in patients with HCC developed from CHB (P < 0.05). Hsa-144-3p/hsa-miR-21-5p exhibited greater performance than alpha-fetoprotein (AUC 0.780, 95% CI 0.601–0.960, versus AUC 0.626, 95% CI 0.410–0.843) in ROC curve analysis. Conclusion: Extracellular vesicle-associated hsa-miR-21-5p and hsa-miR-144-3p are markedly elevated in serum of patients with HCC. The potential role of these microRNAs in the pathogenesis of HCC is worth of further study.